The Interaction Potential of Retigabine (Ezogabine) with Other Antiepileptic Drugs - J. Tompson, Debra; S. Crean, Christopher (Current Clinical Pharmacology, 2014)
Background: Retigabine is an antiepileptic drug (AED) that reduces neuronal excitability by enhancing neuronal KCNQ (Kv7) potassium channel activity. Methods: This manuscript provides an overview of the drug-drug interaction potential of retigabine with other AEDs, using data collated from both in vitro work and clinical studies, either previously published or from relevant information collated during the development of retigabine. Results: Retigabine is not a substrate for the major CYP enzymes and at clinically relevant concentrations there is little or no potential for retigabine to inhibit or induce the CYP enzymes or to inhibit the major renal drug transporters. The addition of retigabine to a range of existing AEDs showed little or no effect on the AED trough concentrations apart from a 20% decrease in lamotrigine concentrations. Results from a small phase II study showed that co-administration of valproic acid and topiramate had no impact on the PK of retigabine whereas carbamazepine and phenytoin increased the clearance of retigabine by approximately 27% and 36%, respectively. Conversely, a population PK analysis of combined data from phase I, II and III studies showed that none of the coadministered AEDs affected retigabine clearance apart from lamotrigine which lowered retigabine clearance by 6.7%. Conclusion: Retigabine is not metabolized by CYP isozymes and does not induce or inhibit these isozymes at clinically relevant concentrations. Therefore, retigabine is associated with a low potential for PK interactions with other drugs via CYP450. Overall, there was little or no potential for retigabine to interact with other available AEDs. Although some PK interactions were observed with lamotrigine, these are unlikely to be clinically relevant.
Keywords: drug-drug interactions